Agriculture Development Programs for Poverty Reduction Evidences from Indonesia and China - Comparative Study Case - Rusliyadi, Muhamad; Libin, Wang (Asian Journal of Agriculture and Rural Development, 2018)
The purpose of this paper is to provide an overview description of important differences in agriculture development China and Indonesia in poverty reduction efforts in rural areas and some strategy. Obviously with the view of some of the existing literature by presenting data and facts or opinions with the collaboration of several institutions associated with the topic. This paper will provide an objective picture of the development from agricultural sector level of evidence both Indonesia and China. China and Indonesia is agriculture based country with a program of integrated rural development as a whole to be a target of poverty reduction programs. Several agriculture programs related to poverty reduction has been launched and have a good impact or significance, especially in China that is able to reduce extreme poverty from 30% in 1978 to less than 3% in 2008. Certainly many lessons can be obtained from this success, especially the concept and strategy development in rural China to be a reference of other States in its development model, especially for poverty alleviation programs.